Menopausal Symptoms in Premenopausal Women Among the Cohort of Gynecological Patients Attending Outpatient Department of Dhulikhel Hospital - Dongol, A.; Deoju, S.; Shikharakar, S.; Rayamajhi, S. J.; Pradhan, N.; Tripathi, P. (Journal of Lumbini Medical College, 2021)
Introduction: Perimenopause is the time when ovaries gradually produce less estrogen. The menopausal symptoms in perimenopausal women cause severe disturbance in the women’s life. This study aimed to identify menopausal symptoms in perimenopausal women. Methods: This was a hospital-based descriptive, cross-sectional study conducted among 243 women aged between 45 to 55 years. The categorical variables were presented as frequency and percentage. The associations between categorical variables were tested using Chi square or Fisher exact test. Result: The total prevalence of menopausal symptoms was 91.8%. Physical symptoms were identified to be prevailing symptom (n=184, 75.7%) followed by psychological (n=167, 69.5%). There were 136 (55.5%) women experiencing poor memory and 148 (60.9%) women having genitourinary symptoms. Stress urinary incontinence (n=73, 30.04%) was predominant over urge (n=58, 23.8%), mixed (n=43, 17.6%) and prolapse (n=49, 20.1%) symptoms. Vasomotor symptoms were experienced by123 (50.6%). Excessive sweating (n=114, 46.9%) was leading over hot flush (n=113, 46.5%), night sweat (n=107, 44.03%) and palpitation (n=96, 39.5%). A total of 114 (46.9%) women were facing sexual symptoms. The common sexual symptom was dyspareunia 68 (27.9%). The Menopausal Rating Scale (MRS) rating of overall symptoms showed women mostly suffer from mild symptoms during the perimenopausal period. Conclusion: Physical symptoms were identified to be predominating followed by psychological, genitourinary, vasomotor and sexual. However rating of symptoms using MRS showed majority of symptoms were mild. This study signifies the need to use the tool for assessment of severity of menopausal symptoms from the perimenopausal group. findings are noted in most of the cases of chronic LBP, degenerative changes being the most common and ranging from congenital to malignant lesions.